Moral Catalyst in Audit: The Selective Role of Auditor's Sense of Responsibility in Strengthening the Effectiveness of Fraud Detection - Krissantono Karo Karo; Cris Kuntadi (Dinasti Publisher, 2026)
This study examines the effect of auditor competence, independence, and experience on fraud detection, with Auditor's Sense of Responsibility (ASOR) as a moderating variable. A survey of 238 external auditors at Public Accounting Firms (KAP) in Jakarta was analysed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with a Higher Order Construct (HOC) approach. Results indicate that competence (β = 0.448; p = 0.000), experience (β = 0.402; p = 0.000), and independence (β = 0.244; p = 0.000) each significantly and positively influence fraud detection. ASOR alone does not significantly affect fraud detection (β = −0.057; p = 0.212). In moderation tests, ASOR does not significantly strengthen the effect of competence (β = 0.003; p = 0.938); however, it partially moderates the effects of independence (β = 0.177; p = 0.000; VAF = 42.0%) and experience (β = 0.214; p = 0.000; VAF = 34.7%). The model explains 67.2% of the variance in fraud detection (R² = 0.672; SRMR = 0.022). This study contributes to forensic audit literature by demonstrating that ASOR functions as a psychological reinforcer that selectively strengthens independence and experience but not technical competence that is already independently internalized.